2023
DOI: 10.1021/acssuschemeng.3c00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Isomers of Thiophenedicarboxylic Acids on the Synthesis and Properties of Thiophene-Based Sustainable Polyesters

Abstract: The need for high-performance bioplastics brings new challenges to the design and preparation of next-generation sustainable bioplastics. With the emergence of a number of biobased monomers with a similar chemical structure in recent years, it is necessary to conduct a systematic and in-depth study on the effects of different isomers of monomers on the final material properties. Considering the potential barrier and bacteriostatic properties of emerging thiophene-based polyesters, this work systematically inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Very recently, Tian et al reported the IL-catalyzed methanolysis of PBTF ( M n = 47.7 kg mol –1 , Đ = 1.6) alongside that of the 3,4-TPCA-derived equivalent (3,4-PBTF; M n = 44.3 kg mol –1 , Đ = 1.4) (Scheme ). Unlike semicrystalline PBTF, 3,4-PBTF is an amorphous polymer with a T g of 17 °C, T d,5% of 372 °C, and low tensile stress (σ b = 0.8 ± 0.1 MPa) but high strain at break (ε b = 1242 ± 41%) . Both polymers were subjected to methanolysis utilizing the IL (7.5 wt %), but lower temperatures and shorter reactions times could be obtained for 3,4-PBTF (PBTF, 130 °C, 5 h; 3,4-PBTF, 110 °C, 1 h).…”
Section: Emerging Aromatic and Aromatic–aliphatic Polyestersmentioning
confidence: 99%
“…Very recently, Tian et al reported the IL-catalyzed methanolysis of PBTF ( M n = 47.7 kg mol –1 , Đ = 1.6) alongside that of the 3,4-TPCA-derived equivalent (3,4-PBTF; M n = 44.3 kg mol –1 , Đ = 1.4) (Scheme ). Unlike semicrystalline PBTF, 3,4-PBTF is an amorphous polymer with a T g of 17 °C, T d,5% of 372 °C, and low tensile stress (σ b = 0.8 ± 0.1 MPa) but high strain at break (ε b = 1242 ± 41%) . Both polymers were subjected to methanolysis utilizing the IL (7.5 wt %), but lower temperatures and shorter reactions times could be obtained for 3,4-PBTF (PBTF, 130 °C, 5 h; 3,4-PBTF, 110 °C, 1 h).…”
Section: Emerging Aromatic and Aromatic–aliphatic Polyestersmentioning
confidence: 99%
“…Recently, researchers have been investigating the replacement of petrochemical terephthalic acid (PTA) with biobased monomers and synthesizing biobased biodegradable copolyesters, which may offer superior performance as packaging materials. , 2,5-Thiophenedicarboxylic acid (TDCA) is a novel aromatic diacid that can be produced from biomass. , Extensive studies have been conducted on TDCA-based homopolyesters, such as poly(ethylene thiophenedicarboxylate) (PETh), poly(propylene thiophenedicarboxylate) (PPTh), and poly(butylene thiophenedicarboxylate) (PBTh). Amorphous PETh has a tensile strength of over 60 MPa and its gas barrier properties are 6–12 times better than those based on PET and even approaching those composed of the well-known 2,5-furandicarboxylic acid (FDCA) . Despite its odd-carbon diol structure, PPTh is surprisingly more crystalline than PETh and PBTh, making it more suitable as a homopolyester base for the synthesis of biodegradable copolyesters with high barrier properties. , In comparison, homopolyesters based on 1,3-propanediol (PDO) and other aromatic diacids, including PTA and FDCA, show inferior crystallinity compared to those based on ethylene glycol (EG) and 1,4-butanediol (BDO). , …”
Section: Introductionmentioning
confidence: 99%
“…Adhesives serve a crucial part in human life and are extensively utilized in the industrial bonding, packaging, building manufacturing, electronic device, and aerospace industries. However, at present, adhesives still face challenges such as poor bond strength (such as epoxy resins), toxicity, irreversible curing (such as acrylics, polyurethanes, and organic silicones), , and limited conditions of use (such as anaerobic adhesives, UV adhesives, and solvent-based adhesives). Polyester hot-melt adhesives are a typical example of solvent-free, ecologically friendly adhesives that meet the demands of the adhesive industry for energy efficiency, nontoxicity, low cost, reusability, and excellent performance. , Linear saturated polyesters are generally utilized as hot-melt adhesives, prepared by transesterification, esterification, and polycondensation reactions, which is simple and easy to process. However, these raw materials used in commercial hot-melt adhesives are usually derived from petroleum resources and do not meet the requirements of sustainable development. Yet, compared to petrochemical products, which come in a large variety, the number of biobased monomers that can be employed to create biomass polyester hot-melt adhesives is substantially fewer. For example, Zheng et al used biobased 1,5-pentanediol as a replacement for petroleum-derived 1,6-hexanediol for polyester hot-melt adhesives . Kim et al prepared a polyester hot-melt adhesive using polybutylene terephthalate modified with dimer acid methyl ester derived from fatty acid methyl esters .…”
Section: Introductionmentioning
confidence: 99%